At the mosque - Al-Marwani, Amatullah (Goodwork Books New Delhi, 2003)
At the Mosque: Zaahir & Jamel the Camel follows a young boy, Zaahir, and his playful camel, Jamel, as they learn about the significance of the mosque in a fun and engaging way. The story introduces children to the mosque$1 (Bs role in the community while teaching respect, manners, and the importance of prayer.s